Development of Hypercontent Module Based on Multiple Representation on Basic Law of Chemistry Material - Mar'atus Solikhah (Jurnal Inovasi Pendidikan Kimia, 2024)
Education in this digital era allows students to learn anytime and anywhere by accessing the internet, so technological advances demand changes in the role of teachers as managers of learning resources, not as learning resources. The lack of understanding of the concept of students on the material of the basic laws of chemistry, which is abstract, is one of the problems in learning chemistry. The development of hyper-content modules based on multiple representations of basic chemical law material is carried out to overcome the shortage of teaching materials. The research and Development (R&D) technique of the 4-D model was used to conduct research at SMAN 5 Semarang, which was undertaken only until the development stage. Data collection techniques were in the form of interviews and distributing questionnaire instruments for feasibility and practicality tests. The data from the media expert feasibility test was 89%, the material expert feasibility test was 90%, the practicality test by two chemistry teachers was 96%, and the practicality response by students was 81%. The data shows that this research is categorized as feasible and practical.